Comparison of maintenance, emergence and recovery characteristics of sevoflurane and desflurane in pediatric ambulatory surgery - Manish B Kotwani; Anila D Malde (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Increasing number of pediatric ambulatory surgeries are being carried out in general anesthesia using supraglottic airways (SGAs). Literature comparing sevoflurane and desflurane for the maintenance of SGA-based anesthesia is limited. Hence, we planned this prospective randomized study to compare the maintenance, emergence and recovery characteristics of sevoflurane and desflurane for pediatric ambulatory surgery. Material and Methods: Sixty children aged 6 months to 6 years posted for short surgical procedures were enrolled into the study. Anesthesia was induced with intravenous propofol (maximum 4 mg/kg), SGA was inserted, and children were randomized to receive sevoflurane or desflurane for the maintenance of anesthesia. No muscle relaxants were administered, and all children received caudal block and rectal paracetamol suppository. Demographic data, perioperative hemodynamics and adverse events, emergence and recovery characteristics, postoperative pain, and emergence agitation (EA) were recorded. Data were analyzed using SPSS (version 16.0, IBM Corporation, Armonk, New York, USA). P < 0.05 was considered statistically significant. Results: Demography, perioperative hemodynamics, and duration of inhalational anesthesia were comparable between two groups. There were no respiratory adverse events in either group during maintenance. Time to awakening and time to removal of SGA were shorter with desflurane (5.3 ± 1.4 and 5.8 ± 1.3 min) than sevoflurane (9.1 ± 2.4 and 10.0 ± 1.6 min) (P < 0.0001). Recovery (steward recovery score = 6) was faster with desflurane (18 ± 8.4 min) than sevoflurane (45.3 ± 9.7 min) (P < 0.001). The incidence of EA was 16.7% with desflurane and 10% with sevoflurane (P = 0.226). Conclusion: Desflurane provides faster emergence and recovery in comparison to sevoflurane when used for the maintenance of anesthesia through SGA in children. Both sevoflurane and desflurane can be safely used in children for lower abdominal surgeries.